Benefit-cost analysis of participatory breeding program in Syria - Mustafa, Yasmin; Ceccarelli, Salvatore; Grando, Stefania (2006)
Participatory plant breeding is seen by several scientists as a way to overcome the limitations of conventional breeding by offering farmers the possibility of deciding which varieties better suit their needs and conditions without exposing them to any risk. It exploits the potential gains of breeding for specific adaptation through the selection in the marginal environment. The participation of farmers increases the probability and speed of adoption as well as the breeding efficiency and the effectiveness of the breeding program. The objective of this study is to estimate and compare the benefits and costs of participatory and conventional barley breeding programs. Benefit-cost analysis was used to analyze the costs and benefits of the PPB program at ICARDA and the conventional program at ICARDA and NARS.